Drug and cell delivery for cardiac regeneration. - DUFFY, GARRY (My University, 2015)
The spectrum of ischaemic cardiomyopathy, encompassing acute myocardial infarction to congestive heart failure is a significant clinical issue in the modern era. This group of diseases is an enormous source of morbidity and mortality and underlies significant healthcare costs worldwide. Cardiac regenerative therapy, whereby pro-regenerative cells, drugs or growth factors are administered to damaged and ischaemic myocardium has demonstrated significant potential, especially preclinically. While some of these strategies have demonstrated a measure of success in clinical trials, tangible clinical translation has been slow. To date, the majority of clinical studies and a significant number of preclinical studies have utilised relatively simple delivery methods for regenerative therapeutics, such as simple systemic administration or local injection in saline carrier vehicles. Here, we review cardiac regenerative strategies with a particular focus on advanced delivery concepts as a potential means to enhance treatment efficacy and tolerability and ultimately, clinical translation. These include (i) delivery of therapeutic agents in biomaterial carriers, (ii) nanoparticulate encapsulation, (iii) multimodal therapeutic strategies and (iv) localised, minimally invasive delivery via percutaneous transcatheter systems.
PUBLISHED
Keywords: Drug Delivery